MiR-7 Functions as a Tumor Suppressor by Targeting the Oncogenes TAL1 in T-Cell Acute Lymphoblastic Leukemia - Sun, Hongbo (Technol Cancer Res Treat, 2020)
BACKGROUND: T-cell acute lymphoblastic leukemia is a hematologic malignancy characterized by T-cell proliferation, and in many cases, the ectopic expression of the oncogenic transcription factor T-cell acute lymphocytic leukemia protein 1 (TAL1). MicroRNA-7 has been shown to play a critical role in proliferation, migration, and treatment sensitivity in a diverse array of cancers. In this study, we sought to establish a novel link between microRNA-7 and T-cell acute lymphoblastic leukemia oncogenesis. MATERIAL AND METHOD: To do so, we characterized gene expression of microRNA-7 as well as TAL1 in both T-cell acute lymphoblastic leukemia patient-derived tissue and cell lines, as well as performing functional luciferase assays to assess microRNA-7 binding to the TAL1 3′-untranslated region. We also performed growth, apoptosis, and migration experiments using 3-(4,5-dimethylthiazol-2-Yl)-2,5-diphenyltetrazolium bromide, Annexin V, and transwell assays in the context of microRNA-7 overexpression. RESULTS: We found that microRNA-7 expression is attenuated and inversely correlated with TAL1 expression in TAL1 + T-cell acute lymphoblastic leukemia cells. Additionally, microRNA-7 directly targets and suppresses TAL1 levels. Finally, microRNA-7 overexpression reduces growth, motility, and migration while inducing apoptosis in T-cell acute lymphoblastic leukemia cells, phenotypes that can be rescued by concomitant overexpression of TAL1. CONCLUSIONS: These results indicate that microRNA-7 functions as a potent tumor suppressor by inhibiting the oncogene TAL1 and suggest microRNA-7 could function as a prognostic biomarker and possible therapeutic in the clinical management of T-cell acute lymphoblastic leukemia.